2020
DOI: 10.1093/noajnl/vdaa114
|View full text |Cite
|
Sign up to set email alerts
|

TERT promoter mutation associated with multifocal phenotype and poor prognosis in patients with IDH wild-type glioblastoma

Abstract: Background Although mutations in the promoter region of the telomerase reverse transcriptase gene (TERTp) are the most common alterations in glioblastoma (GBM), their clinical significance remains unclear. Therefore, we investigated the impact of TERTp status on patient outcome and clinicopathological features in patients with GBM over a long period of follow-up Methods We retrospectively analyzed 153 cases of GBM. Six patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
4
23
1
Order By: Relevance
“…The frequency of EGFR alterations in our cohort was lower than that in TCGA and MSKCC cohorts. However, a study from Japan reported that 25.5-33.1% of GBMs have EGFR ampli cations [19,20], which is consistent with our ndings. Recent reports indicate that 14.4-26% GBMs harbor EGFR mutations [2,21]; however, the EGFR mutation frequency in GBMs in our cohort (6.0%) was considerably lower than that in the previous study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of EGFR alterations in our cohort was lower than that in TCGA and MSKCC cohorts. However, a study from Japan reported that 25.5-33.1% of GBMs have EGFR ampli cations [19,20], which is consistent with our ndings. Recent reports indicate that 14.4-26% GBMs harbor EGFR mutations [2,21]; however, the EGFR mutation frequency in GBMs in our cohort (6.0%) was considerably lower than that in the previous study cohort.…”
Section: Discussionsupporting
confidence: 92%
“…[ 3 ] Moreover, TERT p mutation is a poor prognostic factor for glioblastoma. [ 6 , 19 ] At present, the clinical significance of TERT p mutation is unknown in RGNT. RGNT occasionally presents with spontaneous shrinkage,[ 16 ] as observed in Case 1 of the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 TERT promoter mutations have been associated with poor prognosis in IDH wild-type GBM. 21 The described cauda equina lesion thus contains several genetic features expected to facilitate GBM growth.…”
Section: Discussionmentioning
confidence: 99%